An Application of Anaerobic-Aerobic Combined Bioreactor Efficiency in COD Removal - Kavousi, Rezvan; Borghei, Seyyed Mehdi (Geomatics and Environmental Engineering, 2023)
Over the past few decades, anaerobic-aerobic wastewater treatment systems have been widely used in industrial and municipal wastewater treatment. This study was conducted to examine the effects of combined anaerobic-aerobic bioreactors in the removal of chemical oxygen demands (COD) while reducing phosphate concentrations in synthetic wastewater. In this project, a bioreactor with the dimensions of 10 cm × 10 cm × 80 cm with respective Kaldnes packing ratios of 90 and 30% for the anaerobic and aerobic sections was designed. A combined anaerobic-aerobic reactor’s structure made changing hydraulic retention times only possible by adjusting the volume of its aerobic and anaerobic sections. In the first case, the anaerobic and aerobic sections of the reactor occupied 30 and 50 cm of its height, respectively. The height of the anaerobic section decreases to 12.5 cm in the second case. In aerobic and anaerobic sections, pH was within a neutral range, temperature was 37°C. MLSS (mixed liquor suspended solids) was 1220 and 1030 mg/L, and attached growth was 743 and 1190 mg/L respectively. In order to evaluate COD in the wastewater, three different initial phosphorus concentrations were tested: 12.8, 32.0 and 44.8 mg/L, as well as four COD: 500, 1000, 1200 and 1400 mg/L. Considering the results, COD removal is greater than 80% when the valve 2 is in the anaerobic section outlet regardless of the concentration of phosphate. In this case, the best result is for inlet COD of 500, where the reactor can eliminate more than 90%. When the COD concentration reaches 1000 to 1400 ppm, the reactor’s COD removal efficiency declines to 60%.